IMPROVING SELF-EMPOWERMENT AND QUALITY OF LIFE FOR TYPE 2 DIABETES MELLITUS PATIENTS WITH DIABETES EMPOWERMENT EDUCATION BASED ON A HEALTH PROGRAM MODEL AT PONDOK GEDE HOSPITAL IN 2023 - Zuhriah, Siti Arfah; Fauzi, Achmad (HEARTY, 2024)
Diabetes Mellitus is a combination of insulin resistance and abnormalities in insulin production in pancreatic beta cells. The aim of this research is to analyze the effect of health promotion-based diabetes empowerment education on increasing empowerment and quality of life for diabetes sufferers. This research is a quantitative study using an experimental study, namely assessing changes in self-empowerment and quality of life in type 2 Diabetes Mellitus sufferers with a health promotion education approach using a quasi-experiment design, namely comparing 2 groups, between the control group and the treatment group with a sample of 20 people are divided into a treatment group and a control group. The results of the Wilxocon signed rank test statistical test in the treatment group with a significance of p < 0.05 obtained a value of p = 0.005, so these results indicate that in the treatment group there was a significant increase in self-empowerment between before and after the education/health promotion approach was carried out, while the statistical test results The Wilxocon signed rank test in the control group obtained a value of p = 0.916, so these results indicate that in the control group there were no significant changes in self-empowerment and quality of life before and after treatment.